Prostaglandin-endoperoxide synthase-2 deletion affects the natural trafficking of Annexin A2 in monocytes and favours venous thrombosis in mice - Amadio, Patrizia; Tarantino, Eva; Sandrini, Leonardo; Tremoli, Elena; Barbieri, Silvia S. (Thrombosis and Haemostasis, 2017)
Deep-vein thrombosis (DVT) is a common condition that often leads to pulmonary thromboembolism (VTE) and death. The role of prostaglandin-endoperoxide synthase (PTGS)2 in arterial thrombosis has been well established, whereas its impact in venous thrombosis remains unclear. Here, we showed that PTGS2 deletion predisposes to venous thrombosis as suggested by greater clot firmness and clot elasticity, by higher plasma levels of functional fibrinogen, factor VIII and PAI-1 activity, and proved by bigger thrombi detected after inferior vena cava ligation (IVCL) compared to WT mice. PTGS2-/- thrombi have greater fibrin content, higher number of F4/80+, TF+ and ANXA2+ cells, and lower S100A10+ cells. Remarkably, monocyte depletion reduced thrombus size in mutant mice, suggesting an important role of PTGS2-/- monocytes in this experimental setting. Interestingly, PTGS2 deletion reduced membrane ANXA2, and total S100A10, promoted assembly of ANXA2/p50NF-kB complex and its nuclear accumulation, and induced TF in peritoneal macrophages, whereas ANXA2 silencing decreased dramatically TF. Finally, Carbaprostacyclin treatment prevented venous thrombus formation induced by IVCL in mutant mice, reduced the ANXA2 binding to p50NF-kB subunit and its nuclear trafficking, and decreased TF in PTGS2-/- macrophages. PTGS2 deletion, changing the natural distribution of ANXA2 in monocytes/macro-phages, increases TF expression and activity predisposing to venous thrombosis. Interestingly, Carbaprostacyclin treatment, inhibiting nuclear ANXA2 trafficking, controls monocyte TF activity and prevents DVT occurrence. Our data are of help in elucidating the mechanisms by which PTGS2 inhibition increases DVT risk, and suggest a new role for ANXA2 in venous thrombosis.Supplementary Material to this manuscript is available online at www.thrombosis-online.com.
Keywords: Prostaglandin-endoperoxide synthase-2; prostacyclin; annexin-A2; tissue factor; venous thrombosis